L’usage de la photographie dans la constitution de la collection de maquettes de décors et costumes du département des Arts du spectacle (Bn), 1959-1983 - Lara Le Drian Saint-Germès (In Situ)
This article is an examination of an ambitious programme for creating a collection of photographic slides of models of stage sets and of costumes, undertaken at the initiative of André Veinstein and Cécile Gitteau at the French national library, in 1959, prior to the creation of the library’s department of the performing arts, in 1983. The whole project offers a history of models of stage sets and theatre costumes in the performing arts department. It gives some measurement of the growing interest of heritage institutions and researchers for artifacts associated with the theatre and also the developing willingness of theatre professionals to make donations of their archives and drawings. The story is particularly representative of the lasting impact of André Veinstein and Cécile Gitteau who were leading figures in the development and influence of the library’s performing arts collections. Our aim is to show how collecting policies have evolved where stage sets are concerned. The library’s collection of set models is growing richer year by year and allows for the study of theatre history to adopt new lines of approach, underlining the importance of a visual history of theatre sets and costumes and a living memory of the theatrical creators who are now beginning to give their models and archives to heritage institutions.